Breathing signatures of semantic and phonemic verbal fluency and their impact on test performance in a sample of young Norwegian adults. - Malin Gullsvåg; Yoshihiro Itaguchi; Claudia Rodríguez-Aranda (PLoS ONE, 2024)
Verbal fluency (VF) represents an important aspect of intelligence, in which oral word generation is demanded following semantic or phonemic cues. Two reliable phenomena of VF execution have been reported: A decay in performance across 1-minute trial and a discrepancy score between the semantic and phonemic VF tests (VFTs). Although, these characteristics have been explained from various cognitive standpoints, the fundamental role of speech breathing has not yet been considered. Therefore, the present study aims to evaluate the role of respiratory function for word generation in VFTs in healthy individuals. Thirty healthy young adults performed VFTs during definite periods of 1 minute while wearing a pneumotachograph mask. Duration, peak and volume of airflow were acquired during inspirations and expirations. Also, respiratory rate and acoustic data of verbal responses were registered, and accuracy scores were calculated. Each 1-minute trial was divided into four intervals of 15-seconds where parameters were calculated. Repeated measures ANOVAs and repeated measures correlations were used in the statistical analyses. Data revealed that respiratory function was significantly coupled to VF performance mostly during inhalations. Small but constant increments of inhale airflow occurred in phonemic VFT as well as higher peak airflow in both tasks, being higher for semantic VFT. High respiratory rate characterized performance of both VFTs across intervals. Airflow adjustments corresponded to better VF accuracy, while increments in respiratory rate did not. The present study shows a complex interplay of breathing needs during VF performance that varies along the performance period and that notably connects to inspirations.